ESTUDIO DEL BENZOATO DE METILO: CARACTERIZACIÓN Y APLICACIÓN INSECTICIDA EN AEDES SPP. - Castro Luna, Americo (2024)
ESTUDIO DEL BENZOATO DE METILO: CARACTERIZACIÓN Y APLICACIÓN INSECTICIDA EN AEDES SPP.